2017
DOI: 10.1021/jacs.7b02378
|View full text |Cite
|
Sign up to set email alerts
|

Metal and Metal Oxide Interactions and Their Catalytic Consequences for Oxygen Reduction Reaction

Abstract: Many industrial catalysts are composed of metal particles supported on metal oxides (MMO). It is known that the catalytic activity of MMO materials is governed by metal and metal oxide interactions (MMOI), but how to optimize MMO systems via manipulation of MMOI remains unclear, due primarily to the ambiguous nature of MMOI. Herein, we develop a Pt/NbO/C system with tunable structural and electronic properties via a modified arc plasma deposition method. We unravel the nature of MMOI by characterizing this sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 58 publications
3
119
0
Order By: Relevance
“…[2,3] The state-of-the-art fuel cells still rely on the scarce and precious platinum (Pt)-based electrocatalysts to catalyset he ORR, which seriously hinders the large-scale implementation of fuel cells. [5][6][7][8] Amongt hem, the TM-N-C electrocatalysts are regardeda so ne kind of the most promising NPMCs for ORR, duet ot heir relativelyh igh activity and durability. ), metal oxide,m etal sulfide and carbide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] The state-of-the-art fuel cells still rely on the scarce and precious platinum (Pt)-based electrocatalysts to catalyset he ORR, which seriously hinders the large-scale implementation of fuel cells. [5][6][7][8] Amongt hem, the TM-N-C electrocatalysts are regardeda so ne kind of the most promising NPMCs for ORR, duet ot heir relativelyh igh activity and durability. ), metal oxide,m etal sulfide and carbide.…”
Section: Introductionmentioning
confidence: 99%
“…), metal oxide,m etal sulfide and carbide. [5][6][7][8] Amongt hem, the TM-N-C electrocatalysts are regardeda so ne kind of the most promising NPMCs for ORR, duet ot heir relativelyh igh activity and durability. [9] The deliberate investigation of TM-N-C electrocatalysts can be traced back to 1964 when Jasinski found that cobalt phthalo-cyanine exhibited ORR activity in alkaline electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, forming the metal/oxide interfaces is an extensively studied strategy to enhance the catalytic performance of Pt based catalysts for their favorable effect on down‐shifting d ‐band center of Pt and stabilizing Pt catalysts under ORR condition . In order to reveal the important role of interface in the enhanced ORR performance, people studied the interaction between metal and metal oxide in the Pt/NbO x /C system . According to their results, the interaction between Pt and Nb has no effect on the ORR enhancement, while the interaction between Pt and O improves the ORR performance since it shortens the Pt–Pt bonding.…”
Section: Electrocatalysis Of Interfacial Engineered Bimetal Based Catmentioning
confidence: 99%
“…The obtained catalyst exhibited high mass activity and specific activity compared with the commercial Pt/C catalyst; this result was mainly due to the synergistic effect of Ni doping and the strong interaction between the Pt layer and the support [10]. Mukerjee and co-workers designed a Pt/NbO x /C system as an ORR catalyst and demonstrated that the Pt─O interactions improved the ORR activity [26]. Ultrathin Rh-doped Pt nanowires synthesized by Zeng and co-workers achieved remarkable activity and durability toward the ORR due to the doping of the Rh atoms and high utilization efficiency of the Pt atoms [27].…”
Section: Pt-based Active Sitesmentioning
confidence: 99%
“…Earlier studies have focused on tuning the surface structure [6][7][8] and electronic structure [9] of Pt as well as the electrocatalyst supports [10,11] to achieve optimum ORR activity by using the least amount of Pt. In addition, various kinds of catalysts, including transition metals and their alloys, transition metal oxides/nitrides/sulfides, as well as mixed-valence metal oxides [12,13], carbon-based metal-free catalysts [14], and others have been developed to promote the sluggish kinetics of the ORR at the cathode.…”
Section: Introductionmentioning
confidence: 99%